A PRAGMATIC ANALYSIS OF THANKING STRATEGIES AMONG INDONESIAN EFL LEARNERS BASED ON SOCIAL STATUS AND SOCIAL DISTANCE - Siti Kustini; Iis Sulyaningsih (Jurnal Bahasa Inggris Terapan, 2016)
This study attempts to investigate thanking strategies used by Indonesian EFL learners based on contextual factors i.e. social status and social distance. The participants were 50 semester three students studying English for Business at a state polytechnic in Bandung. The participants were both male and female, aging from 19-20 years old. Data were collected via a Discourse Completion Task (DCT) adopted from Cheng (2005) and analyzed using thanking strategy taxonomy proposed by the same author. The DCT consisted of ten different scenarios describing the most common situations that students may encounter in their college life. The results of this study indicated that the most preferred thanking strategies used by Indonesian EFL learners were thanking, alerters (i.e., title) and positive feelings.  In terms of social status and social distance, the findings revealed that thanking and apology strategies were the most used strategies in equal-status with low-familiarity situations.  In situations within which learners shared equal-status with high-familiarity, the most strategies employed were thanking and positive feelings. Regarding thanking strategies used in low-status with low-familiarity situations, thanking and repayment strategies seemed to be the most preferred ones.  Keywords: thanking, strategies, social status, social distance